"Do I Know You?" Altering hairstyle affects facial recognition. Issue 3 (16th March 2018) - Bartel, Sara J.; Toews, Kelsi; Gronhovd, Lennae; Prime, Steven L.
ABSTRACT: Background: Research has demonstrated that both internal features (e.g., eyes) and external features (e.g., hair) are important for recognizing unfamiliar faces; however, the impact of altering hairstyle on the recognition of unfamiliar faces has yet to be isolated and investigated in the absence of deep processing.Objectives: We sought to examine the extent to which altering hair impacts the recognition of a previously viewed face.Methods: Participants were presented with a series of face images followed by a recognition probe of either a new face or a face that was among the previously presented images with either the same hairstyle (identical face) or a different hairstyle (disguised face).Results: Participants showed significantly less accuracy in the disguised condition compared to the identical condition.Conclusions: Our results provide evidence that hairstyle plays a role in recognizing unfamiliar faces. This appears to hold true across race and sex, as well as across deep and shallow processing.